2011
DOI: 10.1104/pp.111.174110
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response Is Triggered by a Plant Viral Movement Protein    

Abstract: Infection with Potato virus X (PVX) in Nicotiana benthamiana plants leads to increased transcript levels of several stress-related host genes, including basic-region leucine zipper 60 (bZIP60), SKP1, ER luminal binding protein (BiP), protein disulfide isomerase (PDI), calreticulin (CRT), and calmodulin (CAM). bZIP60 is a key transcription factor that responds to endoplasmic reticulum (ER) stress and induces the expression of ER-resident chaperones (BiP, PDI, CRT, and CAM). SKP1 is a component of SCF (for SKP1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
168
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(190 citation statements)
references
References 81 publications
15
168
0
Order By: Relevance
“…The prior analysis was of a large population, and while the median values were lower, the values obtained in this smaller experiment, fall within the range of values obtained from the larger population. 19 These data argue that PVX infection did not require synthesis of molecular markers occurring throughout the ER and secretory pathway. Thus, if membrane synthesis and expansion is occurring during PVX infection, we cannot state that there is a concomitant change in ER-Golgi network markers.…”
Section: Role Of Unfolded Protein Response In Plant Virus Infectionmentioning
confidence: 84%
See 3 more Smart Citations
“…The prior analysis was of a large population, and while the median values were lower, the values obtained in this smaller experiment, fall within the range of values obtained from the larger population. 19 These data argue that PVX infection did not require synthesis of molecular markers occurring throughout the ER and secretory pathway. Thus, if membrane synthesis and expansion is occurring during PVX infection, we cannot state that there is a concomitant change in ER-Golgi network markers.…”
Section: Role Of Unfolded Protein Response In Plant Virus Infectionmentioning
confidence: 84%
“…[16][17][18] Real time RT-PCR analyses revealed an increase in ER resident chaperones which we initially hypothesized could due to expansion of the ER network or that increased levels of chaperones are needed in response to PVX infection. 15,16,19 Thus, (e.g., IRE1, PERK and ATF6). 1,6 BIP is known to be upregulated by bZIP60 and is also reported to regulate cytotoxic damage to cells.…”
Section: Role Of Unfolded Protein Response In Plant Virus Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some external stimuli such as heat stress, salicylic acid treatment, and viral infection have been reported to activate bZIP60 and bZIP28 (Deng et al 2011;Gao et al 2008;Moreno et al 2012;Nagashima et al 2014;Ye et al 2011;Zhang et al 2015). Furthermore, it was reported that an Arabidopsis mutant defective in both IRE1A and IRE1B genes grown under high temperature contains less viable pollen grains, indicating the importance of the UPR in pollen development under high temperature (Deng et al 2016).…”
mentioning
confidence: 99%